Sacred forests as repositories of local biodiversity in Africa: A systematic review - Sinthumule, Ndidzulafhi Innocent (Forest science and technology, 2024)
Sacred forests (SFs) also known as sacred groves are common in many parts of the world and have been protected through traditional methods. In Africa, the number of published studies on the significance of SFs in biodiversity conservation has constantly increased. This offers an opportunity to deploy a systematic review. This study aimed to carry out the first review of SFs in Africa to apply a systematic approach. A systematic literature search on the role of SFs in biodiversity conservation was conducted on Scopus and Google Scholar databases, and additional searches of articles were carried out manually in the reference lists. The search produced 61 papers in 19 countries in Africa that were published between 1995 and 2022. Majority of studies on SFs (44%; n = 27) reported in the reviewed literature were from West Africa as compared to other regions. Methodologically, 80% (n = 49) of reviewed studies lack comparative data with non-sacred areas. A great majority of papers (69%; n = 42) focused on the role of SFs in the protection of plant species, particularly at local/regional scales with no study conducted at international level. Although SFs have great potential for in situ conservation, they are increasingly threatened by anthropogenic pressure. To avoid further threats to SFs, custodians should be legally recognised as owners of SFs and efforts should be made to ensure that SFs are granted juristic personhood. Government should support the protection of SFs and recognise them in a way similar to the recognition given formal protected areas as they also protect vulnerable, threatened and critically endangered species. Existing policies that embrace cultural and religious practices should be implemented to help protect the remaining SFs.